Virtual Implementation of Mobile-Game Based Learning: Enhancing Students’ Vocabulary Mastery and Self-Motivation - Jihan Nawal Aini; Ulfatul Ma’rifah (ELT Worldwide: Journal of English Language Teaching, 2021)
This paper is based on a research on students’ vocabulary mastery at the first grade students of Junior High School at Loeitadnonputtana School, Loei Thailand using Mobile-Game Based Learning strategy. This research is conducted based on the preliminary study which indicated that the students faced some difficulties in mastering English vocabulary. The purpose of this research is to enhance students’ vocabulary mastery through Mobile Game Based Learning. The data were collected by quiz, teacher made-tests, observation, and questionnaire. The data were analyzed by using triangulation. The research design used on this study is Classroom Action Research (CAR). The result of this study shows that Mobile Game Based Learning can significantly enhancing students’ vocabulary mastery from 72% into 86%. Mobile Game Based Learning also makes the students enjoy in learning vocabulary so that they feel motivated and interested more in learning and mastering vocabulary.